2006
DOI: 10.1158/1535-7163.mct-05-0543
|View full text |Cite
|
Sign up to set email alerts
|

Intracellular uptake and intracavitary targeting of folate-conjugated liposomes in a mouse lymphoma model with up-regulated folate receptors

Abstract: The folate receptor is overexpressed in a broad spectrum of malignant tumors and represents an attractive target for selective delivery of anticancer agents to folate receptorexpressing tumors. This study examines folate-lipid conjugates as a means of enhancing the tumor selectivity of liposome-encapsulated drugs in a mouse lymphoma model. Folate-derivatized polyethylene glycol (PEG 3350 )-distearoyl-phosphatidylethanolamine was post-loaded at various concentrations into the following preparations: radiolabele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
71
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 123 publications
(81 citation statements)
references
References 20 publications
10
71
0
Order By: Relevance
“…With regard to folate density, maximal FR-dependent uptake of both NL and SL was obtained previously with a density of 0.2 to 0.5 mol% F-PEG-DSPE (10,17,28,29). Our data on cellular uptake and in vitro cytotoxicity indicated that 0.25 mol% F5-PEG-DSPE in liposomes was optimal for targeting to FR on KB cells.…”
Section: Resultssupporting
confidence: 71%
See 1 more Smart Citation
“…With regard to folate density, maximal FR-dependent uptake of both NL and SL was obtained previously with a density of 0.2 to 0.5 mol% F-PEG-DSPE (10,17,28,29). Our data on cellular uptake and in vitro cytotoxicity indicated that 0.25 mol% F5-PEG-DSPE in liposomes was optimal for targeting to FR on KB cells.…”
Section: Resultssupporting
confidence: 71%
“…In a nonsolid tumor, the high therapeutic efficacy of folate-linked liposomal doxorubicin was reported in mouse ascites leukemia models, in which the treatment route was intraperitoneal injection (14). In addition, the therapeutic efficacy of intravenous treatment with folate-linked liposomal doxorubicin was improved in mice inoculated intraperitoneally with lymphoma cells (32,33). Therefore, further study is needed for FR targeting of solid tumors by intravenous injection of folate-linked liposomes.…”
Section: Resultsmentioning
confidence: 99%
“…In brief, unmodified nanoparticles (NPs) were prepared from Gd-DTPA-bis-stearylamide/PEG 2000 29,36) Cy7-labeled NPs were prepared via the addition of 0.01 mol% Cy7-PEG 2000 -DSPE to NPs or F-NPs. The lipids were dissolved in chloroform-methanol 4 : 1 (v/v).…”
Section: Methodsmentioning
confidence: 99%
“…110,116 In vivo, folate targeting of liposomes has shown the ability to increase the quantity of nanomedicine associated with J6456 lymphoma cells by 17-fold relative to nontargeted liposomes. 117 It must be noted that activated macrophages also express the FR, so it is possible that the therapeutic activity of the liposomes is partially due to targeted elimination of FR-expressing tumor-associated macrophages. 118 High expression of FRs suggests that the folic acid requirements of the cell are high and that appropriate chemotherapeutics may be utilized in order to fully exploit this characteristic.…”
Section: Exploiting Unique Cell Characteristics At the Tumor Level Fomentioning
confidence: 99%